Papercraft Method as Stimulation of The Development of Fine Motor Skills in Early Childhood - Ifalahma, Darah; Yuliana, Ana; Dinawati Aulia, Syaifira; Md Yatim, Nurulshyha (LPPM Universitas Duta Bangsa Surakarta, 2024)
One of the efforts to create a quality generation is by providing stimulation from an early age (4-6 years) to optimize children's golden age so that they grow into individuals who are cognitively intelligent, affectively capable and psychomotor skilled. One aspect of development that needs to be stimulated is the motor aspect. Fine motor skills are the ability to move small muscles such as fingers, especially those that require precision, eye and hand coordination. One interesting way of stimulating fine motor skills is the papercraft method. This research aims to determine the effectiveness of the papercraft method on the development of fine motor skills in early childhood. The research design uses a quantitative experimental one group pre-post test method. The sampling technique is purposive sampling. The sample was 23 group A kindergarten students (4-5 years). The research instrument used papercraft media and fine motor assessment sheets. The research stages consisted of 3 stages, namely stage I pretest, stage II providing intervention and stage III posttest. The data analysis used was the t-test. The results of the research before being given intervention on children's fine motor skills were in the majority in the Starting to Develop category (65.2%), and after being given the intervention the majority were in the Very Well Developing category (47.8%). The results of data analysis t-Count > t-Table means that there is a significant difference in children's fine motor skills before and after being given papercraft stimulation. Conclusion: The papercraft stimulation method is effective in improving the fine motor skills of young children.